Assembly and synthesis of the extracellular matrix in brown algae. (30th January 2023) - Mazéas, Lisa; Yonamine, Rina; Barbeyron, Tristan; Henrissat, Bernard; Drula, Elodie; Terrapon, Nicolas; Nagasato, Chikako; Hervé, Cécile
Abstract: In brown algae, the extracellular matrix (ECM) and its constitutive polymers play crucial roles in specialized functions, including algal growth and development. In this review we offer an integrative view of ECM construction in brown algae. We briefly report the chemical composition of its main constituents, and how these are interlinked in a structural model. We examine the ECM assembly at the tissue and cell level, with consideration on its structure in vivo and on the putative subcellular sites for the synthesis of its main constituents. We further discuss the biosynthetic pathways of two major polysaccharides, alginates and sulfated fucans, and the progress made beyond the candidate genes with the biochemical validation of encoded proteins. Key enzymes involved in the elongation of the glycan chains are still unknown and predictions have been made at the gene level. Here, we offer a re-examination of some glycosyltransferases and sulfotransferases from published genomes. Overall, our analysis suggests novel investigations to be performed at both the cellular and biochemical levels. First, to depict the location of polysaccharide structures in tissues. Secondly, to identify putative actors in the ECM synthesis to be functionally studied in the future.